Sposoby wyrażania opinii o przedmiocie i stanie badań w opracowaniu naukowym z dziedziny prawa autorstwa Michała Bobrzyńskiego (XIX w.) = Methods of expressing opinions on the subject and state of research in a scientific study in the field of law authored by Michał Bobrzyński (XIX century) - Pałucka-Czerniak, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is devoted to the implementation of scientific discourse in the text from the first half of the 19th century, in the scientific sub-discipline of the history of law. The analysed text is perceived as a communication event, occurring in the human community, conditioned by a specific social and cultural context.
Keywords: język; narracja; dyskurs naukowy; historia prawa; language; narrative; scientific discourse; history of law